(untitled) (Ciencias Económicas, 2024)
The main purpose of this article is to carry out an exhaustive characterisation of a multidisciplinary dialogue between the encyclicals Laudato si and Fratelli Tutti, exploring their alignment with the solidarity and ecological economy as viable alternatives to face 21st-century challenges, both in the socio-economic and the socio-environmental spheres of planet Earth. This is a qualitative research work, supported by a documentary review method based on matrices and complemented with search equations derived from the bibliometrics of analytical categories. Its main conclusion highlights that the dialogue between the aforementioned encyclicals and the solidarity and ecological economy approaches has led to a significant broadening of the academic agenda. This exchange has fostered interdisciplinary research that comprehensively addresses the connections between the environmental crisis, social justice and economy. This complex approach has significantly contributed to a profound understanding of the intricacies involved in the search for sustainable solutions.